Modeliranje informacijskih sistemov z upoštevanjem elementov dinamike realnega pojava (Informatica (Ljubljana), 1987)
In this paper an approach to computer supported infomation system design is presented. With described approach we can solve the problems of system consistency with occur in case of usual design when in separated ways is approached to the data base design and to the programs design.
Keywords: baze podatkov; business systems; computer application; computer program; computer science; data base; data model; informacijski sistemi; information systems; model podatkov; modeli; models; podpora; poslovni sistemi; projects; projekti; računalniški programi; računalništvo; support; uporaba računalnikov